Perspectives of older patients on the preventability of their unplanned emergency department return visit within 30 days in the Netherlands: a multicentre mixed methods study - Gert P Westert; Steef van den Broek; Yvonne Schoon; Gijs Hesselink; Özcan Sir; Marije Roordink; Odette Willems (BMJ Open)
Objective Older adults are prone to unplanned emergency department (ED) return visits (URVs). Knowledge about patient perspectives on the preventability and reasons for these URVs is limited and lacks a representable ED study population. This study aims to determine the proportion of URVs and to explore the preventability and underlying causes as perceived by a wide range of older adults and their caregivers.Design A multicentre mixed-methods study.Setting The ED of one academic and one regional hospital in the Netherlands.Participants Patients aged ≥70 years with a URV within 30 days after the index ED visit, consecutively sampled during a 6-week period.Outcome measurements Quantitative data regarding patient and clinical characteristics and perceived preventability of a URV were prospectively collected and analysed using descriptive statistics. Underlying causes of a URV were collected by semistructured interviews with patients and caregivers. Thematic content analysis was used to analyse the interview transcripts.Results Out of 1291 patients of 70 years and older, 151 patients had a URV (11.7%). In total, 64 patients were included after informed consent (42.4%). A total of 33 patients (51.5%) found their URV preventable. Perceived causes for a URV were categorised in six themes: (1) suboptimal treatment of health complaints, (2) premature hospital discharge, (3) poor assessment and arrangement of postdischarge needs, (4) patient and caregiver behaviour, (5) lack of advance care planning and insight in treatment options and (6) deficits in general practitioner care.Conclusions Our high rate of preventable URVs (51.5%) perceived by patients and caregivers underscores the importance to reduce URVs among older adults. Perceived causes in this study add other unexplored themes to the existing knowledge and create support for further research and interventional opportunities.